Co-metabolism based adaptation of anaerobes to phenolic saline wastewater in a two-phase reactor enables efficient treatment and bioenergy recovery. (1st November 2021) - Ali, Manal; Elreedy, Ahmed; Fujii, Manabu; Tawfik, Ahmed
Graphical abstract: Highlights: Co-metabolism adaptation in PB-CBR efficiently removed phenol from saline effluents. Biodegradability of 98% and MY of 0.3 L/gCOD were achieved at phenol up to 0.9 g/L. Sudden/consistent increase of phenol to 2 g/L caused negligible removal within 50 d. Key phenol-degraders, e.g., Syntrophaceae, shifted at different experimental runs. Economic feasibility of PB-CBR was confirmed with minimum payback period of 4.5 y. Abstract: Anaerobic biological treatment of saline phenolic wastewater has some limitations such as slow adaptation, low biodegradability, and salinity-derived washout of biomass, though this technology has some benefits in terms of bioenergy recovery, simplicity in operation, and economic rationality. Therefore, we propose a packed-bed circular baffled reactor (PB-CBR) along with a co-metabolism strategy for phenol adaptation at salinity level of 10 g-NaCl/L. Phenol and glucose were gradually increased and decreased to 0.9 and 1.0 g/L, respectively. Stable and efficient performance was achieved with > 99.9% phenol removal, ∼98% overall biodegradability, and ∼ 0.3 L CH4 /gCOD. A sudden increase in phenol to 2 g/L was then examined, where phenol removal dropped to ∼ 19% after 30 d; after another 30 d, the removal was negligible even when phenol was decreased to 1.7 g/L. The compartment-wise analysis of PB-CBR showed that phases-separation, along all compartments, maintained the overall efficiency, particularly when facing salinity or phenol shocks; otherwise, earlier compartments achieve ∼ 95% of efficiency. The microbial community analysis showed that Corynebacteriaceae, Syntrophaceae, Kosmotogaceae, and Synergistaceae were key players in phenol-degradation. Using readily biodegradable co-substrate enhanced the biodiversity. Eventually, and according to a cost-benefit analysis, the present work offers a promising opportunity to treat phenol-based saline effluents in an efficient, sustainable, and affordable way.